Research in finance. Vol. 25 - Chen, Andrew H. (Emerald, 2009)
This volume contains contributions on a range of important issues in current research in finance and economics. Topics include the design of a country's financial safety nets, the effective policies of acquiring failed banks in reducing moral hazard problems, the voluntary disclosure of real options by corporate managers, and the interrelationship between the housing and general economic activities. Some important topics such as the choice between stock and options as compensation vehicles in the presence of bankruptcy risk, the NUA tax benefits in asset allocation in the retirement accounts, the heuristic approach of using ri/stdi to select securities in forming efficient portfolio, and the arbitrage opportunity in index options at the initial stage are also included in this volume. Finally, the contributions to this volume also address some problems that include the explanations of risk premiums on futures contracts, the optimal hedging decision in futures markets, and the pricing of Asian options subject to credit risk.
Keywords: Finance -- Research.; Banks and banking.; elektronické knihy; electronic books